Mechanochemical efficient recovery of cobalt from spent lithium-ion batteries (LiBs) by chloride solutions - X. Li; Q. Z. Liu; H. H. Yu (Metalurgija, 2024)
Herein, a mechanochemical approach was developed for recover the cobalt and from spent lithium-ion batteries using a high-concentration chloride solution. Effect of parameters on the leaching efficiency of cobalt was studied. 97, 6% of Co was recovered under optimum conditions: rotation speed 500 r/min, S/L ratio: 1:150 g/ml, ball/material ratio 25:1 g/g, milling time 30 min, respectively. The dissolved cobalt was recovered by selective precipitation method to ensure that the recycled Co can be reused for lithium-ion battery production. This research presents a highly efficient and environmentally friendly approach for recovering cobalt from spent LiBs.